The complexity and contradictions of the right to refuse to do hazardous work in the surgical center of a hospital. - Calvo, Daniel de Souza Costa; Ferreira, João Alberto; Cunha, Daisy Moreira; Mendes, Davidson Passos (Work, 2022)
BACKGROUND: The topic right to refuse to do hazardous work/to be exposed to serious and imminent risks is herein presented as the central and fundamental axis on issues associated with workers' health and safety. OBJECTIVE: Investigating how the topic right to refuse to do hazardous work/be exposed to serious and imminent risks may be used as condition and strategy to manage work in the Surgical Center of a hospital. METHODS: The research methodology focused on establishing dialogue among Activity-centered Ergonomics (Ergonomic Workplace Analysis –EWA), Ergology, Action-Research and Ethnography. Samples were collected from March to September 2018 and comprised 120 hours of data, in total. The Surgical Center of the investigated hospital was the place of choice to conduct the study. Assistive Nurses accounting for managing and operating the entire sector were the analyzed population. RESULTS: The concept of refusal was expanded and (re)signified beyond the workers' health and safety perspective, since it was also linked to variables such as environment, quality of products/processes and social accountability. CONCLUSIONS: Refusal does not only mean not doing what is requested, but performing the task requested by other means and paths that are always guided by one's commitment to achieve the overall proposed productive outcomes. The right to refuse is more than a management tool, it is a broad and effective work organization strategy.